Anti-Fungal Drug Anidulafungin Inhibits SARS-CoV-2 Spike-Induced Syncytia Formation by Targeting ACE2-Spike Protein Interaction - Ahamad, Shahzaib; Ali, Hashim; Secco, Ilaria; Giacca, Mauro; Gupta, Dinesh (Frontiers in Genetics, 2022)
Drug repositioning continues to be the most practicable possibility to treat COVID-19 patients immediately. Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV2) virus enters target cells by binding to the ACE2 receptor via its Spike (S) glycoprotein. We used molecular docking-based virtual screening approaches to categorize potential antagonists halting ACE2-Spike interactions utilizing 450 FDA-approved chemical compounds. Three drug candidates (i.e., Anidulafungin, Lopinavir and Indinavir) were selected, which show high binding affinity towards the ACE2 receptor. The conformational stability of selected docked complexes was analyzed through Molecular Dynamics (MD) simulations. The MD simulation trajectories were assessed and monitored for ACE2 deviation, residues fluctuation, the radius of gyration, solvent accessible surface area and free energy landscapes. The inhibitory activities of the selected compounds were eventually tested in-vitro using Vero and HEK-ACE2 cells. Interestingly, besides inhibiting SARS-CoV-2 S-induced syncytia formation, anidulafungin and lopinavir also blocked S-pseudo particle entry into target cells. Altogether, anidulafungin and lopinavir ranked as the most effective amongst all the tested drugs against the ACE2 receptor-S interaction. Based on these findings, we propose that anidulafungin is a novel potential drug targeting ACE2, which warrants further investigation for COVID-19 treatment.